Lecture 3—Measuring Pharmacy’s Work in the 21st Century - Parrish, Richard H. (Pharmacy (Basel), 2018)
The importance of developing a thoroughly shared understanding of mission, vision, and values is highlighted in reference to the creation of meaningful and sustainable key performance indicators (KPIs). A review of clinical practice KPIs (cpKPIs) and operational KPIs (opKPIs) is provided using work load measurement activities from Canada, its province of Alberta, and the United Kingdom. In order for Singaporean pharmacy clinicians and leaders to embrace a unified KPI system, the natural tendency to measure what is easy and available, instead of what matters to patients, is difficult but must be overcome.